H∞ filtering for switched systems subject to stochastic cyber attacks: A double adaptive storage event-triggering communication - Qi, Yiwen; Zhao, Xiujuan; Huang, Jie (Applied mathematics and computation, 2021)
•New results of filtering problem for switched systems with a double adaptive storage event-triggering strategy are given.•A double adaptive storage event-triggering strategy is proposed. Threshold and amount of stored data can be adjusted.•The weight of each accumulated data in the data buffer is different. New released data is more important than old ones.•The impacts of stochastic cyber attacks and transmission delays are considered in switched filtering error system. This paper concentrates on event-triggered filtering for networked switched linear systems subject to stochastic cyber attacks.A double adaptive storage event-triggering strategy (DAS-ETS) is developed. On the one hand, it can automatically adjust the amount of stored data to obtain a weighting error that more dependents on performance changes. On the other hand, its threshold is also adaptively changeable depending on system performance. Both make the strategy more accurately reflect changes in system performance requirements to trigger ‘more necessary’ events. Moreover, actual factors that stochastic cyber attacks and transmission delays are taken into account in the modeling of time-delay filtering error system. Based on Lyapunov functions and average dwell time approach, a set of criteria is provided to guarantee the realization of H∞ performance of filtering error system. Furthermore, the sub-filter gains and DAS-ETS parameters can be calculated by solving a set of linear matrix inequalities (LMIs). At last, a numerical simulation is given to confirm the advantages of the proposed solution.